Is a low concentration of Linoleic Acid related to the extended longevity of the Queen honeybee? - Cocchi, Massimo; Lercker, Giovanni; Frega, Natale Giuseppe; Gabrielli, Fabio; Quaranta , Marino (Progress in Nutrition, 2019)
Lifespan has been a topic of scientific interest for about a century and, in this regard, hundreds of theories have been expressed, calling into question numerous causes of aging, but none of which appears to be decisive. Different species can have hugely different species-specific life spans, but several eusocial species, e.g. honey bees, show very large differences in infra-specific longevity, that is, of individuals. One of the most widely accepted theory remains that of free radicals formulated by Dennis Harmann in 1956 in the historical work “Aging: A Theory based on Free Radical and Radiation Chemistry” (1) and in the following works, where the hypothesis foresees the existence of a strong metabolic activity in the production of free radicals, both on polyunsaturated fatty acids and on proteins with accumulation of oxidized products and damage at mitochondrial level. The effects of peroxidative damage seem to emerge as one of the factors most influencing lifespan. None of the works related to this longstanding problem, however, takes into consideration Linoleic Acid (C18: 2 n-6) as a central element among membrane fatty acids in the involvement of its peroxidation in relation to lifespan. In the examination of the main metabolic responsibilities of Linoleic Acid, attention is focused on the particular role that it, an essential fatty acid, could have as a determining element in the lifespan of worker honeybees with respect to the queen honeybee. Highlights. >Linoleic Acid is an essential fatty acid for mammalian life. >Linoleic Acid occupies a central position in the vital dynamics of animal and human organisms. >Linoleic Acid has the maximum “bulk” in the space within cellular membranes when compared to all the other polyunsaturated fatty acids. >High concentrations of Linoleic Acid can increase the risks of oxidation of Linoleic Acid itself by increasing the peroxidation index, more linked to Linoleic Acid rather than to other polyunsaturated fatty acids.